Improving Students Speaking Skills Through Role Play Strategy - Guwa, Anjelita; Astuti, Endang Setiyo; Rosa, Chindy Hanggara (Journey: Journal of English Language and Pedagogy, 2023)
This study aims to improve the speaking skills of Grade VIII students at SMPS St. Petrus Lokatadho through the implementation of the Role Play strategy. Previously, students faced difficulties in communicating fluently, lacked confidence, and frequently used their mother tongue due to monotonous teaching techniques. This research employed a Classroom Action Research design conducted in two cycles, utilizing both qualitative and quantitative data collection methods. The results demonstrated a significant improvement in students' speaking proficiency. The average score increased from 72.85 in Cycle I to 79.47 in Cycle II. Furthermore, the number of students achieving the success criteria rose from 12 students in the first cycle to 17 students in the second cycle. It is concluded that the Role Play strategy effectively motivates students, minimizes passivity, and enhances active involvement in speaking activities.